(untitled) (Journal of the Bangladesh Association of Young Researchers, 2011)
The purpose of this writing is to guide and facilitate the students, faculty members as well as professionals of University of the Punjab to identify ways and means to prevent plagiarism among academic writing and to develop an awareness of ethical writing. In addition this article will highlight the efforts being carried out by the Higher Education Commission of Pakistan combined with the University of the Punjab in order to curtail plagiarized and questionable writing in academic research. DOI: 10.3329/jbayr.v1i1.6842 Journal of Bangladesh Association of Young Researchers Vol.1(1) 2011 pp.127-132